Spontaneous regression of lumbosacral disc- A case report - Dasgupta, Sibaji; Mukherji, Sushmita (Asian Journal of Medical Sciences, 2020)
Spontaneous regression of lumbar disc is a rare phenomenon. There is no exact described mechanism behind such event. Follow up of such cases in adequate numbers are also lacking. Here we present a case of spontaneous regression of lumbosacral disc prolapse along with resolution of symptoms. A 36 year old lady came to the Out Patient Department (OPD) with sudden onset severe low back pain along with radiation to left lower limb. Magnetic Resonance Imaging (MRI) scan of lumbosacral spine showed a left posterolaterally extruded and inferiorly migrated L5-S1 disc with compression over respective nerve root. She was counseled and possible treatment options were explained. She refused surgery and continued conservative management even knowing all the merits and demerits. Her symptoms improved over time and she had a pain free life for almost two and a half years. Then she experienced mild low back pain again and reviewed at the OPD. Further MRI scan showed significant regression of previously prolapsed L5-S1 disc. Hence, spontaneous regression of prolapsed discs may occur and should be included during counseling of patients with prolapsed disc. But the serious complications of prolapsed discs like muscle weakness and cauda equina syndrome should also be explained along with.